The gut microbiome in bullous pemphigoid: implications of the gut-skin axis for disease susceptibility - Liu, Xiaolin; van Beek, Nina; Cepic, Aleksa; Andreani, Nadia A.; Chung, Cecilia J.; Hermes, Britt M.; Yilmaz, Kaan; Benoit, Sandrine; Drenovska, Kossara; Gerdes, Sascha; Gläser, Regine; Goebeler, Matthias; et al. (Frontiers in Immunology, 2023)
Bullous pemphigoid (BP) is an autoimmune blistering disease that primarily affects the elderly. An altered skin microbiota in BP was recently revealed. Accumulating evidence points toward a link between the gut microbiota and skin diseases; however, the gut microbiota composition of BP patients remains largely underexplored. Here, we investigated the gut microbiota of 66 patients (81.8% firstly diagnosed) suffering from BP and 66 age-, gender-, and study center-matched controls (CL) with non-inflammatory skin diseases (132 total participants), using 16S rRNA gene and shotgun sequencing data. Decreased alpha-diversity and an overall altered gut microbial community is observed in BP patients. Similar trends are observed in subclassifications of BP patients, including first diagnoses and relapsed cases. Furthermore, we observe a set of BP disease-associated gut microbial features, including reduced Faecalibacterium prausnitzii and greater abundance of pathways related to gamma-aminobutyric acid (GABA) metabolism in BP patients. Interestingly, F. prausnitzii is a well-known microbiomarker of inflammatory diseases, which has been reported to be reduced in the gut microbiome of atopic dermatitis and psoriasis patients. Moreover, GABA plays multiple roles in maintaining skin health, including the inhibition of itching by acting as a neurotransmitter, attenuating skin lesions by balancing Th1 and Th2 levels, and maintaining skin elasticity by increasing the expression of type I collagen. These findings thus suggest that gut microbiota alterations present in BP may play a role in the disease, and certain key microbes and functions may contribute to the link between gut dysbiosis and BP disease activity. Further studies to investigate the underlying mechanisms of the gut-skin interaction are thus clearly warranted, which could aid in the development of potential therapeutic interventions.